GEOGRAPHICALLY WEIGHT REGRESSION APPLICATIONS FOR SPATIAL ANALYSIS OF INEQUALITY IN CENTRAL JAVA - Lia Miftakhul Janah; M. Saifudin Nur; Tiani Wahyu Utami (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Inequality is a state where there is an imbalance between each other. Inequality indicates the unevenness ofdevelopment that runs in an area. In Central Java, the problem of inequality among people still exists in daily life.Geographically Weight Regression method is a method that yields model parameter estimators that have localizedproperties at each point or location. In this study aims to modeling the inequality problem that occurred in CentralJava using Geographically Weight Regression method that has the nature of localization at the point. Data takenfrom Central Statistics Agency (BPS) 2015. Through Geographically Weight Regression method can beconcluded that with OLS method got 2 variables effect on imbalance wit h α 10% is variable of HDI  (IPM) andPDRB. While the influential GWR method is the number of population and the amount of labor. While goodnessof fit test showed there is no difference between GWR model and OLS model or in other words there is no spatialeffect in the imbalance analysis in Central Java Province (0.4976 <0.1).Keywords: inequality, GWR,Spatial